(untitled) (Research, Society and Development, 2021)
The aim of this study was to conduct a literature review on neonatal candidiasis and candidemia, addressing etiopathogenesis, epidemiology, virulence factors, risk factors, clinical manifestations, diagnosis, treatment, prevention, immune response, susceptibility to antifungals, strategies for reduction of morbidity and mortality and future perspectives. Articles published in the last ten years in the PubMed, Medline and Google Scholar databases were listed. Candidiasis and neonatal candidemia are important causes of morbidity and mortality worldwide, so that more than 750,000 cases are registered annually. The most susceptible newborns are premature, low birth weight, immunosuppressed, using catheters, mechanical ventilation and parenteral nutrition. Stricter control of risk factors within the hospital environment associated with the care of professionals is required, in addition to the rational use of antifungals in the prevention or treatment of candidiasis and candidemia. It is also important to highlight the gradual change in the epidemiological course of these pathologies due to the emergence of new non-albicans species that can represent a serious risk for neonates. Public policies aimed at the proper management of candidiasis and candidemia are necessary.